Richtigstellung der Schildlausnamen in der Bearbeitung von Schmutterer, Kloft und Lüdicke im ’Handbuch der Pflanzenkrankheiten’ (V. Bd., 5. Aufl., 4. Liefg., 1957). - Lindinger, Leonhard (Contributions to Entomology = Beiträge zur Entomologie, 1958)
The above publication is to rectify names of scale insects incorrectly used by Schmutterer & Kloft in Sorauer’s Handbuch für Pflanzenkrankheiten, Coceidae, 1957. Some additions are given concerning wax-producing species of the genus Ceroplastes and a presumptive way of respiration in some scale insects.